Small-sided games are more enjoyable than high-intensity interval training of similar exercise intensity in soccer - Selmi, O.; Ouergui, I.; Levitt, D. E.; Nikolaidis, P. T.; Knechtle, B.; Bouassida, A. (Open Access Journal of Sports Medicine, 2020)
Introduction: High-intensity interval training (HIIT) and small-sided games (SSG) have been applied and tested for athletes in order to enhance the soccer performance. For this reason, this experimental study aimed to compare the effects of SSGs and HIIT on power, physiological responses and perceived enjoyment. Materials and Methods: Sixteen youth soccer players (age, 17.5± 0.6 years, mean±standard deviation; height, 178.2± 6.4 cm; body mass, 70.4± 5.4 kg; body fat, 10.6± 0.8%) completed one session each of HIIT and SSG on separate days with 1 week between sessions. Each session lasted 25 mins (4x4 mins work with 3 mins of passive recovery in-between). SSGs consisted of 4 versus 4 player games on a 25× 35 m pitch, and HIIT consisted of intermittent 15-s runs at 110% maximal aerobic speed separated by 15 s of passive recovery. Psychological responses following each protocol were assessed using the Physical Activity Enjoyment Scale (PACES). Heart rate (HR) was continuously recorded, rating of perceived exertion (RPE) and lactate concentration [La] were measured after each training session. Lower body muscular power was assessed using the 5-jump test relative to leg length (5JT-relative) before and after each training session, where greater average distance per stride over five sequential jumping strides indicated greater muscular power. Results: HIIT and SSG showed no significant difference in HR, RPE and [La] responses (p=0.70, ES=0.11; p=0.61, ES=0.08 and p=0.38, ES=0.21, respectively). 5JT-relative decreased significantly for SSG and HIIT (p< 0.05, ES=0.50 and p< 0.05, ES=0.40, respectively). PACES score was greater in SSG compared to HIIT (ES=5.35, p< 0.001). Conclusion: HIIT and SSG sessions induced similar physiological responses; however, SSGs induced a higher enjoyment level than HIIT. Coaches could choose between these training modalities according to the objective of their training session, considering the enjoyment-related advantages of SSGs.